Central-Local Government Relations in Thailand : Improving Service Delivery - World Bank (Bangkok, 2014)
Addressing regional disparities in access to public services is an emerging development challenge for Thailand. A well-functioning system of Central-Local Government Relations and proactive expenditure policy can help achieve this goal. Providing responsive and accountable public services are necessary for maintaining trust of the citizens in government and fostering cohesion within a unitary state like Thailand. Without a reversal of current regional disparities in access to public services and addressing tensions that are present in the central-local architecture, Thailand runs the risk of eroding public trust in government and leading to further polarization. Thailand has a significant opportunity to improve delivery of public services by: (i) making access to public services more uniform across the country; (ii) transitioning fully to a unitary decentralized form of government with clearly demarcated roles and accountability structures between different levels of government (especially within health and education sectors) and to administratively consolidate Laos into larger more financially viable entities; and (iii) establishing national service delivery standards, publishing annual performance reports on these benchmarks along with unit costs of standard goods and supplies procured, and publishing reports on operations at the municipal level.